(untitled) (Raparin Journal of Humanities (RJH), 2025)
The main aim of this study is to survey the issue of the writing format of numbers in mathematics class (based on the lecturer’s and teachers’ opinions) in the Kurdistan Region’s (KR) curriculum which is writing format from right to left. After discussions on the subject with university lecturers and public school teachers in the Koya District, at first, an open-ended questionnaire was prepared and conducted with the participation of 20 teachers, and on this base, the main questionnaire was prepared to survey the issue. After obtaining the face validity of the questionnaire from the specialized experts, the survey was distributed to (55) teachers of mathematics, physics, chemistry, and English language majors. As a result, a positive view of the sample’s statistical evidence regarding the presence of specific issues was obtained. Demographically, there was no difference in positive perceptions of university lecturers and public school teachers towards this issue. However, the responses of mathematics class teachers were more positive than that of other specialties. In addition, the demographic variable of the teaching service has had an effect in favor of those teachers who have had fewer years of teaching service.